Achievements of Muslims in the field of science and technology - Islam, Arshad (National Academy of Sciences of Azerbaijan, Institute of Mathematics and Mechanics, Baku Azerbaijan Republic, 2011)
A history of Muslims’ contribution to present-day science and technology is the exploration of the missing account of their glorious past. The Prophet Muhammad’s (SAW) arrival opened a new epoch in the history of the Arabs. Soon after, Muslims successfully conveyed the message of Islam from the Arabian Peninsula to the Iberian Peninsula and from the frontiers of China to India. Muslims integrated science, theology, and philosophy as they were urged to study, acquire knowledge, and learn from others' expertise and civilization. They thus excelled in medicine, mathematics, astronomy, geometry, geology, mineralogy, chemistry, philosophy and architecture, and it was their greatest achievement to establish trigonometry as a distinct branch of mathematics. Muslim scholars began acquiring Greek treatises and initiated their study and rendering into Arabic. They examined critically, collated, corrected and enriched significantly major texts of Greek science and philosophy. The ensuing era started what is known as the Golden Age of Islam, which lasted for over two centuries. The present study is an attempt to examine the contribution of Muslim scientists, philosophers and theologians in the promotion of science and scientific research in various periods of history. Based mainly on Arabic, Persian, Urdu and English sources, the study focuses on the intellectual legacy of the Muslims, their interest in the progress of science and philosophy and its impact on the West.